Religious Stories We Live By : Narrative Approaches in Theology and Religious Studies. - Ganzevoort, R. Ruard (Brill, 2013)
Religious Stories We Live By offers philosophical, psychological, and epistemological reflections on the importance of narrative, case studies, and disciplinary overviews of narrative perspectives in biblical, empirical, systematic, and historical approaches in theology and religious studies.